In vitro antifungal activity of Turbinaria conoides collected from Mandapam coast, Tamilnadu, India - Shibu, A; Dhanam, S. (Journal of Experimental Sciences, 2016)
ABSTRACT Marine macroalgae have been used as medicines or drug sources for a great many years, stretching back to the era of folk medicines. Algae have been extensively used in the traditional medicines of maritime nations for treatment of goitre, cancer, hypertension, cough and other diseases. The present work was carried out to find out the antifungal activity of the seaweed Turbinaria conoides collected from Mandapam coastal regions of Tamilnadu. The extracts were tested against Candida albicans, Candida parapsilopsis, Fusarium sp, Aspergillus flavus , Asergillus fumigatus. The hexane, chloroform and ethanolic extracts showed a well profound inhibitory activity against Candida albicans and Candida parapsilopsis. No inhibitory activity was found at Fusarium sp, Aspergillus flavus , Asergillus fumigates under chloroform and ethanolic extracts. Key words: Medicine, antifungal, cancer, Candida albicans, diseases.